Cost-utility analysis of HIV screening in blood donors using a decision-tree Markov model - HUANG Liqin; WANG Lilin; WU Linfen; ZUO Jiahui; ZENG Jinfeng (Zhongguo shuxue zazhi, 2025)
[Objective] To develop a comprehensive health economics evaluation model for HIV blood screening using Markov modeling, so as to evaluate the quality-of-life adjustment years (QALYs) gained by transfusion recipients after implementation of blood HIV screening. [Methods] Shenzhen Blood Center was selected as the validation case for model development. Based on historical HIV screening data of Shenzhen Blood Center and published literature, the health economics evaluation of donor HIV screening was performed using cost-utility analysis. The single factor sensitivity analysis was performed on parameters in the model. [Results] 3.09 QALYs were gained for each transfusion recipient prevented from HIV infection. During 2020-2023, donor HIV screening at Shenzhen Blood Center saved 506.76 QALYs, and each QALY saved 182 900 yuan. [Conclusion] From the perspective of long-term benefit of transfusion recipients, HIV screening of blood donors demonstrates high health and economic value.